Evolution of Genome Size in Duckweeds (Lemnaceae). (28th July 2011) - Wang, Wenqin; Kerstetter, Randall A.; Michael, Todd P.
Abstract : To extensively estimate the DNA content and to provide a basic reference for duckweed genome sequence research, the nuclear DNA content for 115 different accessions of 23 duckweed species was measured by flow cytometry (FCM) stained with propidium iodide as DNA stain. The 1C-value of DNA content in duckweed family varied nearly thirteen-fold, ranging from 150 megabases (Mbp) in Spirodela polyrhiza to 1, 881 Mbp in Wolffia arrhiza . There is a continuous increase of DNA content in Spirodela, Landoltia, Lemna, Wolffiella, and Wolffia that parallels a morphological reduction in size. There is a significant intraspecific variation in the genus Lemna . However, no such variation was found in other studied species with multiple accessions of genera Spirodela, Landoltia, Wolffiella, and Wolffia .